Clinically Significant Minor Blood Group Antigens amongst North Indian Donor Population - Divjot Singh Lamba; Ravneet Kaur; Sabita Basu (Advances in Hematology)
Background. Racial differences in blood group antigen distribution are common and may result in striking and interesting findings. These differences in blood group antigen distribution are important due to their influence on the clinical practice of transfusion medicine. Study Design and Methods. This is a prospective study, involving 1000 healthy regular repeat voluntary blood donors associated with the department. The clinically significant minor blood group antigens of these donors were studied. Results. Out of 1000 healthy regular repeat voluntary blood donors, 93% were D positive and 2.8% were K positive. Amongst the Rh antigens, e was the most common (99%), followed by D (93%), C (85.1%), c (62.3%), and E (21.5%). Within the MNS blood group system, antigen frequency was M (88%), N (57.5%), S (57.8%), and s (87.5%). Within the Duffy blood group system, antigen frequency was Fya (87.3%) and Fyb (58.3%). Conclusions. This data base will help us to prevent alloimmunisation in young females, pregnant women, and patients who are expected to require repeated transfusions in life by providing them with antigen matched blood. Antigen negative blood can also be made available without delay to already alloimmunized multitransfused patients.